Pengaruh Model Pembelajaran Kooperatif Jigsaw dan Komando terhadap Hasil Belajar Lari 100 Meter ditinjau dari Motivasi Belajar pada Siswa Kelas 7 SMPN 1 Dusun Selatan - Munadi Munadi; Sumaryanto (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This research aims to determine the effect of the jigsaw cooperative learning model on the learning outcomes of 100-meter running of seventh-grade students of SMPN 1 Dusun Selatan (Dusun Selatan 1 Junior High School),  the effect of the command model on improving the learning outcomes of 100-meter running of seventh-grade students of SMPN 1 Dusun Selatan, the effect of learning motivation on improving the learning outcomes of 100-meter running of seventh-grade students of SMPN 1 Dusun Selatan, and (4) the simultaneous effect of the jigsaw cooperative learning model and command on the learning outcomes of 100-meter running of seventh-grade students of SMPN 1 Dusun Selatan. The type of this research was an experiment with a 2X2 factorial. The research population was seventh grade students of SMP Negeri 1 Dusun Selatan. The sample was taken by using a stratified sampling technique totaling 64 students, from class 7A for the jigsaw cooperative learning model and 7B. for the command model. Then 27% of the participants were taken with high learning motivation and 27% with low learning motivation for each Jigsaw and Command learning model. The research findings reveal: (1) from the results of the Paired Samples T Test, a Sig. Value of 0.000 < 0.05 is obtained, meaning there is a significant effect after being given the jigsaw cooperative model treatment in class 7 A. With a mean pretest of 62.5000 and a mean posttest of 83.1875. The mean difference is at 20.68750. (2) For the Command Model, the Sig. Value of 0.000 < 0.05 meant there is a significant effect after being given the command model treatment in class 7 B. With a mean pretest of 54.875 and a mean posttest of 81.0625. The mean difference is at 26.37500. Hence, the difference is accepted because there is a significant difference before and after treatment. (3) The results of the jigsaw group motivation test are 0.693 > 0.05, meaning there is no any effect between learning motivation and student learning outcomes. This means Ha is rejected and Ho is accepted. Therefore, there is no any significant effect between learning motivation and 100-meter running learning outcomes for seventh-grade students of SMPN 1 Dusun Selatan. (4) The 2-tailed Sig value is 0.000 < 0.05. The mean value between the pretest and posttest is at 7.711. Therefore, it can be concluded that there is a simultaneous effect between the jigsaw cooperative teaching model, the command style, and learning motivation on 100-meter running learning outcomes  Keywords: Jigsaw cooperative model, command model, learning motivation.